Application Research on DOA Estimation Based on Software-Defined Radio Receiver. (August 2020) - Li, Zuokun; Zhang, Dongdong; Zhu, Qichao; Gu, Henghao; Huang, Shuai; Kuang, Yi; Liu, Yingwen
Abstract: Using a KerberosSDR, with four omnidirectional antennas and a raspberry pi, a four-element system of direction of arrival estimation system is formed. The four antennas are arranged in accordance with a uniform linear array and a uniform circular array respectively. Four algorithms including Bartlett, Capon, MEM, and MUSIC are used. Finally, the MUSIC algorithm is used to estimate the direction of arrival of the static target signal source, and the results are displayed on the map.